Measurement of phase equilibrium characteristics and optimization of state equation for N2-CO2 binary system - Naiya XIE; Feng YAN; Jianlu ZHU; Junwen CHEN; Lei CHENG; Qihang WANG (You-qi chuyun)
Objective The presence of impurities impacts the phase equilibrium of CO2, potentially compromising the safety of CO2 pipeline transmission. As efforts intensify towards advancing the application of Carbon Capture, Utilization and Storage (CCUS) technology, examining the phase equilibrium of impurity-containing CO2 systems is essential for the broader adoption of this technology. Methods An experimental setup was independently developed to measure the phase characteristics of impurity-containing CO2 systems, utilizing the compressibility difference between gas and liquid phases. This setup allows for the measurement and calculation of pressure at the bubbling and dew points for impurity-containing CO2 systems over the temperature range of -30℃ to 50℃. The experimental results were compared with simulations generated by the PR equation, GERG-2008 equation, BWRS equation, SRK equation, and PRSV equation to assess their predictive accuracy. Results For N2-CO2 binary systems with varying ratios, the predictive accuracy of all these state equations for pressure at the bubbling and dew points diminished as the N2 content increased. Additionally, the predictive accuracy varied across temperature intervals for these equations. Specifically, the PR equation demonstrated enhanced accuracy in pressure prediction at both the bubbling and dew points below 0℃, compared to predictions above 0℃. Conversely, the GERG-2008, SRK, and PRSV equations displayed an opposite trend. Furthermore, the BWRS equation consistently exhibited low predictive accuracy for this system across all ratios, without any identifiable pattern. Conclusion Taking into account the predictive accuracy trends of equations across different temperature intervals, excluding the BWRS equation which lacks any discernible pattern, optimization recommendations are suggested for these state equations. For pure CO2, it is advisable to utilize the PR equation below 0℃ and the PRSV equation above 0℃. In the case of a mixture comprising 99.5% CO2 and 0.5% N2, the PR equation is recommended for use within the temperature range of -20℃ to 20℃. Similarly, for a mixture of 96% CO2 and 4% N2, both the PR equation and PRSV equation are recommended for use within the temperature range of -30℃ to 20℃.